THE INFLUENCE OF OLEFIN CONTENT IN GASOLINE AGAINST DEPOSIT BUILD UP ON INTAKE VALVE OF MOTOR BIKE ENGINE - Nur Ahadiat; Djainuddin Semar (Testing Center for Oil and Gas LEMIGAS, 2010)
The specification of gasoline 91, according to Dirjen Migas decree No. 3674 K/24/DJM/2006 dated March,17 2006 define the limit (maximum) of aromatic content 50%volume, and benzene 5.0% volume, but does not define boundary for olefin content as its is regulated in others countries. Olefin compound happened to be saturated hydrocarbon, its has higher octane number, unstable, produces gum that later on could build up as deposit on intake valve of combustion chamber or nozzle tip of fuel injection system. The objective of this study was to know how far the influence of olefin content in gasoline 91 to deposit build-up in intake valve of motor bike engine after cruising on road test for certain distance. For this purpose, the motor bike will be fueled with gasoline 91 with olefin content variations and will be compared to motor bike that cruised at the same route and distance accumulation with regular gasoline 91. Effect of several volume variety of olefin content in gasoline againts deposit development of intake valve engine will be discuss in this paper.